Mastering Elliott wave principle : elementary concepts, wave patterns, and practice exercises - Brown, Constance M. (Hoboken, New Jersey : Wiley, 2012)
An innovative approach to applying Elliott Wave Principle By convention, most Elliott Wave Principle (EWP) practitioners focus on individual market price movement. Connie Brown has a global reputation of developing analysis that focuses on the integration of global markets. In a two book series you will be taken through the steps to master the global cash flows of today's financial markets. The approach found in this first book differs from the traditional view of EWP because it shows you how geometry and the use of simple boxes drawn within a trend will guide you away from the common complain.
A Summary of Rules and GuidelinesA Table of Degree Labels and Names; Beginner Level: Practice Examination; Beginner Level: Final Examination; Exercise Appendix; About the Author; Index.
Includes index.
Description based on print version record.
Keywords: Elliott wave principle; Speculation; Stocks; Elliott wave principle; Speculation; Stocks; BUSINESS & ECONOMICS -- Investments & Securities -- General; Elliott wave principle; Speculation; Stocks; Electronic books; Electronic books